The pharmacology of blinatumomab: state of the art on pharmacodynamics, pharmacokinetics, adverse drug reactions and evaluation in clinical trials. (29th July 2022) - Mocquot, Pauline; Mossazadeh, Yasmine; Lapierre, Léopoldine; Pineau, Fanny; Despas, Fabien
Abstract: What is known and objective: Bispecific drugs (BDs) belong to the family of immunotherapies along with checkpoint inhibitors and CAR‐T cells. In the field of oncology, BDs are designed to simultaneously bind a tumour antigen on the one side and an antigen present on the surface of effector cells on the other. This review summarizes the information available to date on the first marketed BiTE‐format bispecific antibody, blinatumomab BLINCYTO® in acute lymphoblastic leukaemia. Methods: A literature search was conducted in the PubMed database by including studies published in English using the term blinatumomab. Furthermore, bibliographies of selected references were also evaluated for relevant articles. Clinical trial (CT) data were retrieved from clinicaltrials.gov (ongoing trials, adverse events [AEs]) and global pharmacovigilance data were retrieved from VigiBase®. Results and discussion: Blinatumomab is a fusion protein which consists of two single‐chain variable fragments arranged in tandem: the first binds the CD19 surface antigen of all B cells and the second targets the CD3 antigen of T cells. Binding of blinatumomab to B and T cells induces apoptosis of B cells after secretion of granzymes and perforins by T cells. T‐cell activation results in secretion of pro‐inflammatory cytokines and upregulation of activation markers and adhesion molecules on the surface of T cells. The major CTs that led to an indication show increased overall survival with blinatumomab with better efficacy in patients in haematological remission with minimal residual disease ≥10 −3 . The major AEs are cytokine release syndrome, neurotoxicity and hypogammaglobulinemia. The three most frequent system organ classes in CTs are haematological, gastrointestinal and general disorders. These results are also found in VigiBase® but neurological disorders and infections appear more frequently in real life. What is new and conclusion: This review summarizes the current knowledge of blinatumomab in the literature. The subject of many CTs is to improve the route of administration and expand the indications for treatment. Abstract : Blinatumomab has been the subject of many clinical trials and the scientific data are scattered across different works. This review summarizes the information available to date on the first marketed BiTE‐format bispecific antibody, blinatumomab BLINCYTO® in acute lymphoblastic leukaemia. Blinatumomab is a fusion protein which consists of two single‐chain variable fragments arranged in tandem: the first binds the CD19 surface antigen of all B cells and the second targets the CD3 antigen of T cells. The major clinical trials that led to an indication show increased overall survival with blinatumomab with better efficacy in patients in haematological remission with minimal residual disease ≥10 −3 . There are many ongoing clinical trials (about 79) with blinatumomab in different diseases. The major adverse events are cytokine release syndrome, neurotoxicity and hypogammaglobulinemia. The three most frequent system organ classes in clinical trials are haematological, gastrointestinal and general disorders. These results are also found in VigiBase® but neurological disorders and infections appear more frequently in real life.